2.354   ODE No. 354

$y'(x) (x \sin (y(x))-1)+\cos (y(x))=0$ Mathematica : cpu = 0.168906 (sec), leaf count = 145

$\left \{\left \{y(x)\to -\cos ^{-1}\left (\frac {c_1 x-\sqrt {-x^2+1+c_1{}^2}}{1+c_1{}^2}\right )\right \},\left \{y(x)\to \cos ^{-1}\left (\frac {c_1 x-\sqrt {-x^2+1+c_1{}^2}}{1+c_1{}^2}\right )\right \},\left \{y(x)\to -\cos ^{-1}\left (\frac {\sqrt {-x^2+1+c_1{}^2}+c_1 x}{1+c_1{}^2}\right )\right \},\left \{y(x)\to \cos ^{-1}\left (\frac {\sqrt {-x^2+1+c_1{}^2}+c_1 x}{1+c_1{}^2}\right )\right \}\right \}$ Maple : cpu = 0.054 (sec), leaf count = 108

$\left \{ y \left ( x \right ) =\arctan \left ( {\frac {1}{{{\it \_C1}}^{2}+1} \left ( -{\it \_C1}\,\sqrt {{{\it \_C1}}^{2}-{x}^{2}+1}+x \right ) },{\frac {1}{{{\it \_C1}}^{2}+1} \left ( {\it \_C1}\,x+\sqrt {{{\it \_C1}}^{2}-{x}^{2}+1} \right ) } \right ) ,y \left ( x \right ) =\arctan \left ( {\frac {1}{{{\it \_C1}}^{2}+1} \left ( {\it \_C1}\,\sqrt {{{\it \_C1}}^{2}-{x}^{2}+1}+x \right ) },{\frac {1}{{{\it \_C1}}^{2}+1} \left ( {\it \_C1}\,x-\sqrt {{{\it \_C1}}^{2}-{x}^{2}+1} \right ) } \right ) \right \}$